Apatite LA-ICP-MS U–Pb and fission-track geochronology of the Caño Viejita gabbro in E-Colombia: Evidence for Grenvillian intraplate rifting and Jurassic exhumation in the NW Amazonian Craton. (March 2020) - Bonilla, Amed; Franco, Jose A.; Cramer, Thomas; Poujol, Marc; Cogné, Nathan; Nachtergaele, Simon; De Grave, Johan
Abstract: The 1.80–1.76 Ga crystalline basement in Colombia as part of the W-Amazonian Craton is composed mainly of gneisses, granitoids and migmatites, affected later by several compressive and extensional events resulting for example in A-type granites, but also mafic intrusions and dikes. Here we present, after a revision of main geological features, research results obtained on the NW-SE trending ilmenite-apatite-rich Caño Viejita gabbro in the SW-Vichada department some 500 km east of Bogota. Petrographic and geochemical data hint to a metaluminous continental alkaline gabbro enriched in K, Ti and P, possibly due to continental crust reworking or magma mixing, as also confirmed by trace elements characteristics in the apatites like HREE enrichment (Ce/Yb)cn 12–13, negative Eu-anomaly, and Y, Th, Sr, Mn ratios. LA-ICP-MS U–Pb apatite geochronology suggests an early Neoproterozoic emplacement age between 975 ± 9 and 1002 ± 21 Ma related with rifting triggered by the Amazonia-Baltica-Laurentia collision during the Rodinia Supercontinent assembly and associated Grenvillian events. These events also caused mafic intrusions in other parts of the craton. Apatite fission track thermochronometry and thermal history modelling on one sample suggest the onset of the final exhumation stage during Jurassic (~180 Ma), which brought the rocks slowly to their current outcrop position. Highlights: LA-ICP-MS U–Pb apatite geochronology as a method for emplacement ages in small intrusions. Rifting triggered by collisions during the Supercontinent formation. Mafic intrusions in the W-Amazonian Craton associated to Grenvillian events. W-Amazonian Craton exhumation stage during Jurassic by Apatite fission track thermochronometry.